WHO Europe evidence based recommendations on the treatment of tobacco dependence. Issue 1 (1st March 2002) - Raw, M; Anderson, P; Batra, A; Dubois, G; Harrington, P; Hirsch, A; Le Houezec, J; McNeill, A; Milner, D; Poetschke Langer, M; Zatonski, W
Abstract : The following recommendations on the treatment of tobacco dependence have been written as an initiative of the World Health Organization European Partnership Project to Reduce Tobacco Dependence.